MARGINALIZATION OF WOMEN LABORERS AT OIL PALM INDUSTRY OF DAMAI JAYA LESTARI COMPANY IN WIWIRANO DISTRICT OF NORTH KONAWE REGENCY, SOUTHEAST SULAWESI - Hafsah, Wa Ode Sitti; Kumbara, A.A. Ngurah Anom; Wiasti, Ni Made; Setiawan, I Ketut (E-Journal of Cultural Studies; Volume 11, Number 2, May 2018, 2018)
This study discusses the forms of marginalization of women laborers at oil palm industry of Damai Jaya Lestari Company in Wiwirano District of North Konawe Regency. The economy factor brings the women to work in public sector as hard laborer because their education level is low. As the result, they often get unjustify action and marginalization. As qualitative method and culture studies, this study aims finding out the forms of marginalization of women laborers at Damai Jaya Lestari Company. In analyzing the data, it used theories of feminism, gender relation, and power relation. To find out the relevant data, the study used participant observation, interview, and documentation. The result of the study shows that the forms of marginalization of women laborers at Damai Jaya Lestari Company are unjustice of laborers recruitment, access of working, closed control of company, low wages, no assurance of health and work accident, bad work tool and facility, and double burden of women laborers. Those are also factors of marginalization of women laborers at Damai Jaya Lestari Company. Although the women laborer get the job in public sectors and has contribution to the family prosperity, it can not change the paradigm of patriarchal culture in the social and culture system of Wiwirano society in North Konawe, including at Damai Jaya Lestari company.